High acetone soluble organosolv lignin extraction and its application towards green antifouling and wear-resistant coating - Wu, Zhipeng; Thoresen, Petter Paulsen; Maršík, Dominik; Matsakas, Leonidas; Kulišová, Markéta; Fous, Karel; Maťátková, Olga; Masák, Jan; Rova, Ulrika; Ytreberg, Erik; Granhag, Lena; Christakopoulos, Paul; et al. (International journal of biological macromolecules, 2024)
Marine fouling poses significant challenges to the efficiency and longevity of marine engineering equipment. To address this issue, developing effective marine antifouling coatings is critical to ensure the economic viability, environmental sustainability, and safety of offshore operations. In this study, we developed an innovative green antifouling and wear-resistant coating based on lignin, a renewable and sustainable resource. Lignin is considered environmentally friendly because it is abundant, biodegradable, and reduces reliance on petroleum-based materials. The coating was formulated with a controlled hydrophilic-to-hydrophobic ratio of 2:8, leveraging lignin's unique properties. Applying lignin increased the water contact angle by 14.5 %, improving surface hydrophobicity and contributing to the coating's antifouling efficacy. Moreover, the mechanical strength of the coating was enhanced by approximately 200 %, significantly boosting its durability in harsh marine environments. Additionally, the friction coefficient was reduced by about 85 %, further preventing organism adhesion. These results demonstrate that lignin-based coatings offer a greener alternative to traditional antifouling solutions. The results of this study not only help advance antifouling coating technology but are also consistent with the broader goal of promoting environmental responsibility in marine engineering practice.
Keywords: hydrofobní a hydrofilní interakce; lignin; povrchové vlastnosti; Polyurethane; Biofouling; aceton; Green Chemistry Technology; Hydrophobic and Hydrophilic Interactions; Surface Properties; Acetone; rozpouštědla; bioznečištění; Solubility; Solvents; Antifouling; rozpustnost; Lignin; technologie zelené chemie; Coating